Determination Of Rare Earth Elements And Its Distribution Pattern From The Core Sediments By Ko-Instrumental Neutron Activation Analysis - Ebenezer Aquisman, Asare; Rafeah, Wahi; Alexander Obiri, Gyampoh; Omolayo Ajoke, Omorinoye (Kalpana Corporation, 2021)
his work aimed to assess rare earth elements and their distribution pattern from the core sediments from the central coast of Ghana by Ko instrumental neutron activation analysis. The rare earth element content was evaluated with uncertainty less than 8% (at 95% confidence level) and demonstrated to be accordant with the IAEA-soil 7 certified concentrations. The calculated concentration of light rare earth elements and Fe normalized enrichment factors suggested that sediment samples were not enriched with light rare earth elements (LREEs) obtained from discharges of anthropogenic activities. The chondrite-normalized pattern of rare earth elements exhibited LREEs, Tm, Tb, Eu and Ho enrichment. The total contents of rare earth elements calculated can be used to establish baseline information about environmental contamination determination and to develop the relationships between the Ce/Ce* and Eu/Eu* anomalies and the source appointment of both LREEs elements and heavy rare earth elements (HREEs).